2014
DOI: 10.1007/s12192-013-0474-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor-modulated Hsp70/AT1 expression may protect the kidneys of SHRs at the structural and functional levels

Abstract: Previous hypertension studies have shown that low levels of vitamin D are linked to elevated renin-angiotensin system. The heat shock protein 70 regulates signaling pathways for cellular oxidative stress responses. Hsp70 has been shown to protect against angiotensin II-induced hypertension and exert a cytoprotective effect. Here, we wanted to evaluate whether the vitamin D receptor (VDR) associated with Hsp70/ AT 1 expression may be involved in the mechanism by which paricalcitol provides renal protection in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Of interest for our finding, melatonin increases Hsp70 and protects the livers of toluene‐exposed rats from oxidative stress‐induced cytotoxicity . Hsp70 regulates antioxidant responses to cellular oxidative stress, and our laboratory showed that Hsp70 reduces the activity and expression of NADPH oxidase . In agreement with our previous findings, we now demonstrate an increase in Hsp70 in melatonin‐treated rats.…”
Section: Discussionsupporting
confidence: 91%
“…Of interest for our finding, melatonin increases Hsp70 and protects the livers of toluene‐exposed rats from oxidative stress‐induced cytotoxicity . Hsp70 regulates antioxidant responses to cellular oxidative stress, and our laboratory showed that Hsp70 reduces the activity and expression of NADPH oxidase . In agreement with our previous findings, we now demonstrate an increase in Hsp70 in melatonin‐treated rats.…”
Section: Discussionsupporting
confidence: 91%
“…These results thus show a novel strategy to prevent UUO-induced kidney damage by using chitosan/siRNA nanoparticles to knockdown COX-2 specifically in macrophages (Yang et al 2015). Moreover, mitochondrial abnormality has been shown in many kidney disease models Diez et al 2015;Manucha 2014;García et al 2014García et al , 2014. However, its role in the pathogenesis of CKD is still uncertain.…”
Section: Hsp70/no Renal Cytoprotective Action As Consequence Of Statimentioning
confidence: 87%
“…NADPH oxidase activity was reverted in mitochondrial fractions from vitamin D inducer-treated animals (García et al 2012a, b). Furthermore, VDR-modulated Hsp70/AT 1 expression may protect the kidneys of spontaneously hypertensive rats (SHR) at the structural and functional levels (García et al 2014). Previously, vitamin D treatment increased Hsp70 expression which was localized to renal tubular cells in the outer medulla (Kim et al 2005).…”
Section: Effect Of Hsp70 On Pro-inflammatory Activation Of Epithelialmentioning
confidence: 99%
“…In SHR, the same renal protective effects were brought about by 4 mo paricalcitol, enalapril, or combined paricalcitol-enalapril treatments. Importantly, both paricalcitol and enalapril improved VDR expression (146).…”
Section: The Klotho-vitamin D-ras Connectionmentioning
confidence: 93%